A Qualitative Methods Approach to Reimagine Education-Related Parental Involvement among Low–Socioeconomic Status Families. Issue 4 (8th September 2022) - Perrigo, Judith L; Hurlburt, Michael; Harris, Taylor; Villamil Grest, Carolina; Borja, Jessica; Samek, Anya
Abstract: Disparities in academic achievement have been well documented between low– and high–socioeconomic status (SES) students in the United States. Studies point to education-related parental involvement as a key factor in academic accomplishments, with higher parental involvement facilitating higher academic achievement. However, current definitions of parental involvement neglect interpretations of parental involvement held by low-SES parents. This work explored these definitions held by low-SES families through focus groups ( n = 10) and individual interviews ( n = 23) with parents of school-age children. Findings suggest that low-SES parents define parental involvement to include the vital role of siblings, limited communication with teachers unless behavioral or academic problems arise, and activating informal enrichment activities. Factors that hindered their involvement include having limited time for engaging in education-related activities and poor proficiency in educational materials. These findings suggest that the concept of parental involvement ought to be conceptualized in more nuanced ways to support the closure of the academic achievement gap between students from low- and high-SES families.